Analyzing the Problems and Solutions for Movie Piracy in Indonesia - Christian, Vincent Dennis (PT FORMOSA CENDEKIA GLOBAL, 2024)
In this digital era, the illegal distribution of intellectual property such as films has flourished especially in Indonesia. Indonesian citizens are also one of the main problems in digital piracy, as most of them still use illegal streaming sites to watch movies on. This research aims to analyze the causes of the culture of watching movies illegally, the constant emergence of illegal streaming sites, the efforts made to combat this phenomenon, and to give the solutions that might help in reducing this phenomenon. After analyzing several articles on this subject, three main causes of watching movies illegally have been identified, they are: watching movies for free, lack of awareness in intellectual property, and the ineffective efforts made by the government to combat illegal streaming sites. Solutions gained from this research are to implement education programs to educational institutes early on to raise a future generation with a better awareness. A collaboration between the Indonesian government, local telecommunications service providers, and official movie streaming platforms could be proposed to help combat piracy by reducing costs to watch a movie legally. Lastly, a piracy detection tool could be implemented to help the government in blocking any illegal streaming sites